Farmers willingness to pay and the sustainability of irrigated maize production in rural Kenya - Ochuodho, Dennis O.; Odhiambo, Nicholas; Bii, Hillary (My University, 2017)
This paper evaluated farmers willingness to pay for irrigated maize production using field level data collected through a cross sectional survey. The results showed that 78% of the farmers were willing to pay more than the men willingness to pay of 3,082. This was above the average payment that farmers were making. It was also noted that willingness to pay increased with increase in irrigation rates. Labour, tail end farms, and enforcement of scheme level rules and regulations will enhance willingness to pay. Efficient factor use is an important factor influencing the amount paid for irrigation. Although the economic value of water was found to be greater than the willingness to pay implying that irrigated maize production is sustainable, irrigation services in Kenya are highly subsidized by the government. We therefore recommend farmer training, empowering water user associations to help enforce irrigation management processes as a way of enhancing farmers’ willingness to pay. On sustainability of irrigated maize production, we recommend that market forces be allowed to establish the price of irrigation services.
http://www.tegemeo.org
Keywords: Willingness to pay; Irrigation; maize; food security; sustainability